Improving CSF Biomarkers’ Performance for Predicting Progression from Mild Cognitive Impairment to Alzheimer’s Disease by Considering Different Confounding Factors: A Meta-Analysis - Ferreira, Daniel; Rivero-Santana, Amado; Perestelo-Pérez, Lilisbeth; Westman, Eric; Wahlund, Lars-Olof; Sarría, Antonio; Serrano-Aguilar, Pedro (Frontiers in Aging Neuroscience, 2014)
Background: CSF biomarkers’ performance for predicting conversion from mild cognitive impairment (MCI) to Alzheimer disease (AD) is still suboptimal. Objective: By considering several confounding factors we aimed to identify in which situations these CSF biomarkers can be useful. Data sources: A systematic review was conducted on MEDLINE, PreMedline, EMBASE, PsycInfo, CINAHL, Cochrane, and CRD (1990-2013). Eligibility criteria: 1) prospective studies of CSF biomarkers’ performance for predicting conversion from MCI to AD/dementia; 2) inclusion of Aß42 and T-tau and/or p-tau. Several meta-analyses were performed. Results: Aß42/p-tau ratio had high capacity to predict conversion to AD in MCI patients younger than 70 years. P-tau had high capacity to identify MCI cases converting to AD in ≤24 months. Conclusions: Explaining how different confounding factors influence CSF biomarkers’ predictive performance is mandatory to elaborate a definitive map of situations where these CSF biomarkers are useful both in clinics and research.